2008
DOI: 10.1007/s10995-008-0321-9
|View full text |Cite
|
Sign up to set email alerts
|

A Multi-Method Assessment of Satisfaction with Services in the Medical Home by Parents of Children and Youth with Special Health Care Needs (CYSHCN)

Abstract: Both the focus groups and surveys demonstrated that families of children with special needs are under very significant stress. Pediatricians must become better equipped to identify and communicate more proactively with families of CYSHCN that are experiencing significant parent burden. Pediatricians and their staff also need to improve their knowledge of community resources and proactively make referrals to community services needed by families of CYSHCN.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
28
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(29 citation statements)
references
References 39 publications
1
28
0
Order By: Relevance
“…Our results, as well as those of other studies [25][26][27], showed that the CSQ-3 items have a good internal reliability for measuring general satisfaction of parents. A common phenomenon of the surveys evaluating satisfaction, including ours, is to produce highly skewed distribution of the satisfaction towards higher levels of satisfaction [14,16,17,25]. This ceiling effect could have occurred in our study because the range of the four-point Likert scale used with the CSQ-3 was probably not broad enough to detect satisfaction variations among individuals with high levels of satisfaction [29].…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…Our results, as well as those of other studies [25][26][27], showed that the CSQ-3 items have a good internal reliability for measuring general satisfaction of parents. A common phenomenon of the surveys evaluating satisfaction, including ours, is to produce highly skewed distribution of the satisfaction towards higher levels of satisfaction [14,16,17,25]. This ceiling effect could have occurred in our study because the range of the four-point Likert scale used with the CSQ-3 was probably not broad enough to detect satisfaction variations among individuals with high levels of satisfaction [29].…”
Section: Discussionmentioning
confidence: 88%
“…Less is known about the parent and child features which could influence satisfaction with care. Several studies suggested that satisfaction with services might be influenced by parental distress, type and severity of the child's disability and the child's lack of improvement [15][16][17]. The aim of this study was to identify parent and child characteristics which could influence parent satisfaction with preventive services designed to detect SL delay early in life.…”
Section: Introductionmentioning
confidence: 99%
“…29 Care coordination conducted as a standard of pediatric practice resulted in increased family satisfaction with the quality of care and also decreased barriers to care. 30 Other data have suggested that the PFCMH represents a process of care that may help families manage the daily demands of caring for children with special health care needs through family-centered care, provider-to-provider communication, and provision of care coordination. 31 A 2011 study in children and youth with special health care needs and their families who received care coordination and individualized care plans via a Medicaid managed care plan study reported improved satisfaction with mental health services and specialized therapies and participants were observed to have a decline in unmet needs, improved satisfaction with specialty care, and improved ratings of child health and family functioning.…”
Section: Benefits Of and Evidence For Care Coordinationmentioning
confidence: 99%
“…5 Despite recent efforts to provide comprehensive care to CSHCN that would maximize health outcomes and improve quality of care, [6][7][8] the effects on satisfaction and family-centered care are unclear. [9][10][11] In addition, although individual characteristics such as race and ethnicity influence reports of satisfaction and family-centered care, 1,[12][13][14] it is unclear how state child health policies and the health care system affect these quality measures.…”
mentioning
confidence: 99%
“…19,20 Insurance also influences satisfaction 10,15,21 and may also influence family-centered care. 6,7,9 One pivotal study of CSHCN revealed that underinsurance and uninsurance predicted lower satisfaction versus CSHCN with insurance, 4 yet it is not well understood how satisfaction varies across insurance types.…”
mentioning
confidence: 99%